Pathological PCI as a prognostic marker of survival after neoadjuvant chemotherapy in patients undergoing interval cytoreduction with or without HIPEC in FIGO stage IIIC high grade serous ovarian cancer - Sinukumar, Snita; Damodaran, Dileep; S., Deepika; Piplani, Sanjay (Frontiers in Oncology, 2024)
Objective: To determine the best possible value of pathological PCI (pPCI) as a prognostic marker for survival in high grade serous epithelial ovarian cancer patients in patients treated with neoadjuvant chemotherapy and interval cytoreductive surgery, Method: All patients with FIGO stage IIIC high grade serous carcinoma of ovary were included. Receiver operating curves (ROC) were applied to the best possible score of pPCI in predicting survival. Survival curves were calculated using the Kaplan-Meier test and factors affecting survival was compared using the log rank test.Results: From Jan 2018 to Jan 2024, 171 patients undergoing interval cytoreductive surgery were included. A complete cytoreduction was obtained in 88% patients. ROC Curves, determined a (pPCI) cut off value of 8 as the best possible score in predicting survival with a sensitivity of 82% and specificity of 67% .(Youden's Index =0.60). pPCI with a cut off value of 8 showed improved OS ( p=0.002) and DFS, (p=0.001) in both univariate and multivariate analysis .Following interval cytoreductive, surgery despite an optimal complete cytoreductive surgery, a pathological PCI of 8 is a poor prognostic indicators of survival and may serve as a surrogate clinical marker for guiding clinicians for adjuvant treatment especially in the real world resource driven setting.Despite a complete cytoreduction after NACT, pathological PCI of 8 is a poor prognostic indicator of survival.